VD_FINDINFO Décision / 2013 / 321 vom 7. April 2013 - VD Tribunal cantonal (2013)
AVOCAT D'OFFICE, DÉFENSE D'OFFICE, AVOCAT, HONORAIRES | 135 al. 3 let. a CPP (CH), 135 CPP (CH), 393 al. 1 let. c CPP (CH)